CD8+ T Cells Trigger Auricular Dermatitis and Blepharitis in Mice after Zika Virus Infection in the Absence of CD4+ T Cells - Lee, Cheryl Yi-Pin; Carissimo, Guillaume; Teo, Teck-Hui; Tong, Samuel Jia Ming; Chang, Zi Wei; Rajarethinam, Ravisankar; Chua, Tze Kwang; Chen, Zheyuan; Chee, Rhonda Sin-Ling; Tay, Alicia; Howland, Shanshan Wu; Ang, Kok Siong; et al. (Journal of investigative dermatology, 2023)
Zika virus (ZIKV) became a public health concern when it re-emerged in 2015 owing to its ability to cause congenital deformities in the fetus and neurological complications in adults. Despite extensive data on protection, the interplay of protective and pathogenic adaptive immune responses toward ZIKV infection remains poorly understood. In this study, using a T-cell‒deficient mouse model that retains persistent ZIKV viral titers in the blood and organs, we show that the adoptive transfer of CD8+ T cells led to a significant reduction in viral load. This mouse model reveals that ZIKV can induce grossly visible auricular dermatitis and blepharitis, mediated by ZIKV-specific CD8+ T cells. Single-cell RNA sequencing of these causative CD8+ T cells from the ears shows an overactivated and elevated cytotoxic signature in mice with severe symptoms. Our results strongly suggest a role for CD8+ T-cell‒associated pathologies after ZIKV infection in CD4+ T-cell‒immunodeficient patients.